MEBEL ANYAM DARI SERAT PELEPAH PISANG DI DESA TRANGSAN SUKOHARJO - Iik Endang Siti Wahyuningsih (Universitas Sebelas Maret, 2020)
One of several weaving furniture center villages is in the village of Trangsan, Gatak District, Sukoharjo Regency. The furniture handicraft business in the village of Trangsan is a business that has long been in the field since 1983 (1984 began to export) and is a hereditary effort from the previous generation. Previously, several studies have been conducted that reveal the existence of export furniture (especially rattan) from the village of Trangsan, but so far the research specifically focused on design studies of furniture using banana fiber fiber material classified as still small in number. While research on the use of banana midrib fiber is more in the process or the product is in the form of souvenir items (such as bags, sandals, tissue boxes, etc.) and not those applied to furniture. Therefore, it would be a consideration for research on furniture exports from this midrib banana fiber. This research is more likely to reveal the problem of the existence of furniture crafts that utilize banana midrib fiber and the potential that can be developed from existing crafts, both in the production process and design development. This research is more focused on the production process and design development, as one of the efforts to solve problems in the field of development through business work in the field of weaving furniture craft by using banana midrib fiber.